The Legality of Unilateral Increase of Interest Rate in Banking Loan Contracts under Serbian Law - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The economic crisis spread in 2008 through the world and reached Serbia, rendered the repayment of banking loans indexed in foreign currencies, mostly in CHF at the time, even more difficult. The growing number of non-performing loans inevitably led to an increase in number of the court proceedings in which the debtors made attempts to have the loan contracts declared null and void. In these proceedings, the courts needed to take a stand on some typical clauses in loan contracts and on some banking practices that the debtors considered to be contrary to the principle of good faith, which, before the crisis, was hardly ever given judicial epilogue. In the majority of cases,  two types of clauses proved to be unlawful: a clause establishing a right of the bank to subsequently, i.e. after the formation of the contract, and unilaterally, i.e. without the consent of the debtor, change (regularly increase) the interest rate for the remainder of the credit period; and a clause establishing the right of the bank to apply different exchange rates, i.e. the buying rate to the disbursement of the loan, and the selling rate to the value of credit installments. These clauses certainly existed even before the crisis, but the difficulties in performing the loans caused by the crisis was the social propelling force that brought these cases within the sight of the judiciary. In this paper the author analyzes the reaction of courts, and subsequently that of the legislator, to the clause in loan contracts entitling the bank to unilaterally increase the variable interest rate after the formation of contract. The application of this clause was usually conditioned on significant changes in international financial markets or changes in the sources of financing, while in some cases the conditions of the application of the clause were simply changes in the business policy of the bank or the need to operate with profit. In any case, these are circumstances which the debtor could not influence. In most cases the bank could have influenced these circumstance or at least taken them into consideration at the time of the formation of contract. If not, they still fall within the bank’s sphere of control or the bank bears the risk of their occurrence. The uniform approach of the courts, both in respect to credit contracts in which the debtor is a consumer, and contracts in which the debtor does not qualify as consumer, is that these clauses in loan contracts are null and void, since they are contrary to principles of good faith and equal value of reciprocal obligations, on the one hand, and make the object of the contract unascertainable, on the other. The courts, however, hardly ever declare the contract null and void in its entirety, but rather apply the rules on partial invalidity. Until the adoption of the Law on the Protection of Financial Services Consumers in 2011, the courts could render their decisions based only on the rules of general contract law pursuant to the Law on Obligations from 1978. The Law on the Protection of Financial Services Consumers explicitly forbids the modification of variable interest rate due to changes in the business policy or internal acts of the bank and prescribes that only officially published data or criteria may be used as variable elements of the interest rate. By this means, stipulating the right of the bank to subsequently, unilaterally and, in fact, freely increase the interest rate, a practice frequently applied in cases in which it was not economically justified, became statutorily forbidden.